1985
DOI: 10.1111/j.1469-1809.1985.tb01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited thermostability variants of seven enzymes in a Japanese population

Abstract: The frequency of inherited variations in thermostability was investigated in a series of seven enzymes in a Japanese population. Among a total of 5930 determinations, nine variants were encountered. In each instance one parent exhibited a similar finding. It is suggested that this procedure should detect a high proportion of the variants of these enzymes characterized by amino acid substitutions not altering molecular charge. Failure to detect more such thermostability variants is interpreted to mean that elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These observations are consistent with those concerning intensities of variant bands in the above described variants where the band of variant homodimer was the least intense of the three bands and that of the heterodimer was tess intense than the homodimer band of 1, except for 1-5NG1 where the intensity of the variant homodimer band which is the most cathodal, was as strong as that of homodimer band of 1. Regarding the thermostability of GOT1 variants, we have already reported that phenotypes 1-2HR1, 1-3NG1 and 1-4NGI have normal or increased thermostability (Satoh et al, 1985). Family studies for these variants confirmed the genetic nature of this characteristic, as shown in Table 6.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…These observations are consistent with those concerning intensities of variant bands in the above described variants where the band of variant homodimer was the least intense of the three bands and that of the heterodimer was tess intense than the homodimer band of 1, except for 1-5NG1 where the intensity of the variant homodimer band which is the most cathodal, was as strong as that of homodimer band of 1. Regarding the thermostability of GOT1 variants, we have already reported that phenotypes 1-2HR1, 1-3NG1 and 1-4NGI have normal or increased thermostability (Satoh et al, 1985). Family studies for these variants confirmed the genetic nature of this characteristic, as shown in Table 6.…”
Section: Resultsmentioning
confidence: 63%
“…Thermostability profiles of variant enzymes were examined as previously described (Satoh et al, 1985) using 1 : 20 diluted hemolysates prepared from packed red cells preserved in liquid nitrogen. Percent remaining activities were determined after heating for 10 and 20 min at 60~…”
Section: Methodsmentioning
confidence: 99%
“…In India, a study to screen newborns with jaundice for the presence of pyruvate kinase deficiency determined that 3.21% of all newborns with jaundice also had the deficiency, with a 30-40% reduction found in pyruvate kinase activity (12) . Screened children of survivors of the atomic bombs in Japan were studied and prevalence values of 1.4% (threshold < 66% of normal) were found among 3069 child (13).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been extended through population studies to other loci (Mohrenweiser and Neel 1981;Satoh et al 1985). Seven different enzyme systems have been studied, and all systems have been found to contain thermostability variants.…”
Section: Stability Variantsmentioning
confidence: 99%
“…We should note that although these rare alleles have low activity, they do not seem to affect the thermostability of the enzyme (Satoh et al 1985).…”
Section: Activity Variants and Null Allelesmentioning
confidence: 99%